2009
DOI: 10.1177/1744987108096969
|View full text |Cite
|
Sign up to set email alerts
|

Preparing the air for nursing care: A grounded theory study of first line nurse managers

Abstract: The first line nurse managers' opportunities to lead nursing care seem to be diminishing. The aim of this study was, therefore, to gain an understanding of the first line nurse managers in their experiences in the development of nursing care as part of a wider research programme. Finnish nurse managers wrote narratives at the beginning of five different leadership courses in this grounded theory study. 'Preparing the Air for Nursing Care' emerged as a core category. It was formed by two major categories. 'Bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(105 citation statements)
references
References 27 publications
(55 reference statements)
6
96
0
3
Order By: Relevance
“…In her research on first line nursing management Bondas found that these leaders, together with the staff, have to prepare the ground for nursing care. Preparing the ground for nursing care is a continuous process for the nursing leaders which is important for the unit's core function, for creating direction and quality in nursing, and with the patient as main focus [27]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In her research on first line nursing management Bondas found that these leaders, together with the staff, have to prepare the ground for nursing care. Preparing the ground for nursing care is a continuous process for the nursing leaders which is important for the unit's core function, for creating direction and quality in nursing, and with the patient as main focus [27]. …”
Section: Discussionmentioning
confidence: 99%
“…They also experience varying support from the managers and that the management does not understand what is going on or what it feels like to be a nurse “right inside the anthill.” Such practice is not compatible with a caritative, nurturing culture which should prepare the ground for good nursing care in the best interest of the patient, relatives, and the nurse [1, 27]. …”
Section: Discussionmentioning
confidence: 99%
“…They must also regularly update their professional management skills to meet ministerial and organizational requirements for optimal management of the work environment for the benefit of nursing staff, on the one hand, and of both accessibility and continuity of care and services for the benefit of the population, on the other. [21] In reviewing the scientific literature, [12][13][14][15][16][17][18][19][20] we found that a significant amount of NM time is spent on the administrative management of operations, including staff training, work schedule management, mentoring, substitutions, completion of forms of all kinds, participation in meetings, drafting of minutes, checking payroll, supervision, and mail delivery. Finally, striking a balance between their clinical and administrative roles was essential for NMs to assume their clinicaladministrative leadership within the organization.…”
Section: Nms' Scope Of Practicementioning
confidence: 99%
“…[11,22] For example, the NMs' administrative role consists of hiring and evaluating the performance of staff nurses, developing departmental budgets, and maintaining inventory of medicines, equipment, and nursing supplies. [11,[20][21][22][23][24] As to the clinical role of NMs, they must be able to mentor nurses' clinical practice, develop education programs, and contribute to the staff's professional development. [20] For example, NMs also use strategies for risk anticipation and assessment to design, implement, and evaluate plans of care for a cohort of patients in a context of infection outbreaks.…”
Section: Nms' Scope Of Practicementioning
confidence: 99%
“…Research has predominantly focused on first-line managers/executives and has explored attributes, traits, competencies, roles and styles, and impact [6]. Nursing leadership has traditionally been linked with transactional leadership, not compatible with professional core values [7].…”
Section: Introductionmentioning
confidence: 99%